Beta-variant recombinant SARS CoV-2 vaccine induces durable cross-reactive antibodies against Omicron BA variants - Odile Launay; Rachna Gupta; Tifany Machabert; Eleine Konate; Alexandra Rousseau; Claire Vigne; Francois Beckers; Louis Devlin; Elisabeth Botelho-Nevers; Marine Cachanado; Christian Chidiac; Dominique Deplanque; et al. (Communications Medicine)
Abstract Background We previously reported the safety and immunogenicity data from a randomized trial comparing the booster responses of vaccinees who received monovalent (MV) recombinant protein Beta-variant (MVB.1.351) and MV ancestral protein (MVD614) vaccines with AS03 adjuvant (Sanofi/GSK) to booster response of vaccinees who received mRNA MV ancestral strain BNT162b2 vaccine (Pfizer-BioNTech). Methods First booster of the vaccines was administered in adult participants previously primed with 2 doses of MV ancestral strain BNT162b2. A subset of these participants with available blood samples collected at Day 0 (D0), at 28 days (D28), and 3 months (M3) post-booster were contacted for additional testing (195/208 participants). The persistence of cross-neutralizing antibodies, including against Omicron BA.1 and BA.4/5, up to 3 months after boosting was evaluated using a validated pseudovirus neutralization assay. Results Across the whole population, MVB.1.351 vaccine induces highest NAbs titers against Omicron BA.1 and BA.4/5 variants at D28 and M3 post-booster. In participants with SARS-CoV-2 infection between D28 and M3, both MVB.1.351 and BNT162b2 vaccine groups show an increase in GMTs against Omicron BA.1 and Omicron BA.4/5 following infection. Among uninfected participants, the ratio of M3 to D28 GMTs was higher for the MVB.1.351 group than the BNT162b2 group against Omicron BA.1 (0.64 [0.53;0.77] versus 0.43 [0.35;0.53]), Omicron BA.4/5 (0.61 [0.50; 0.75] versus 0.44 [0.34; 0.56]), and D614 (0.68 [0.58,0.81] versus 0.46 [0.39,0.55]). Conclusions The MVB.1.351 vaccine induces higher and durable cross-neutralizing antibodies against Omicron subvariants up to 3 months after boosting compared to an MV ancestral and mRNA BNT162b2 booster vaccine.